Compósitos de Matriz Geopolimérica Reforçados com Fibras Vegetais de Abacaxi e de Sisal - Correia, Edvaldo Amaro Santos (2011)
The use of vegetable fibers as a reinforcing agent in geopolymers, represents an alternative to the replacement of manufactured fibers as a reinforcing agent. The pineapple leaf, an abundant plant in the region and with easy cultivation and processing, which produces low modulus of good mechanical performance fibers, emerges as an ecologically viable and sustainable alternative. In this work, fiber ananas comosus and agave sisalana have been characterized by a process of selection, cleaning, washing, drying and cutting of fresh blankets for the production of composites based on geopolymer matrix. The good mechanical performance and the possibility of using industrial waste materials and the abundance of precursors materials of the region favor the use of geopolymer matrix in obtaining the bodies of proof used in this study. The use of vegetable fibers (ananas comosus and agave sisalana) as a reinforcing agent in geopolymer to obtain composites provided gain in quality to the mechanical properties of the matrix. We conclude that the ratio Si / Al is one of the main variables controlling the process of geopolymerization. However, a better relationship of the interface fiber / matrix produces accommodation and better performance with and absorption of considerable effort on the part of the composite. This behavior is influenced by variations in temperature, pressure and flow of geopolymer used as a matrix. During this study, thermal analysis techniques (TG, DTG, DTA), microscopy (MEV) and spectroscopy (XRF, DRX) as well as mechanical and chemical tests were used to characterize the materials used in this work. Also presented are the results of mechanical tests of composites with sisal and pineapple tree fibers, and micro-structural behavior, when it will be possible to compare the benefits of vegetable fiber added to the performance and resistance of bodies of proof.